Vitreomacular Traction and Outer Retinal Structural Changes - Şeyda Yıldırım; Jale Menteş; Mine Barış (Türk Oftalmoloji Dergisi, 2019)

(untitled)
In this case report we aimed to present the outer retinal structural changes secondary to vitreomacular traction (VMT). Outer retinal structural changes occurring secondary to VMT due to incomplete posterior vitreous detachment were described retrospectively with spectral-domain optical coherence tomography in 3 eyes of 3 patients. The patients ranged in age from 58 to 65 years and best corrected visual acuity in the 3 eyes was 4/10, 8/10, and 9/10. All of the patients were symptomatic and exhibited outer retinal microholes at the fovea extending from the retinal pigment epithelium to outer limiting membrane, with an overlying operculum on the detached posterior hyaloid membrane over the macula following spontaneous resolution of VMT. In the mean follow-up period of 32 months, the outer retinal microholes decreased in size but did not completely resolve. As demonstrated in these cases, VMT can cause small outer retinal layer defects without signs of full-thickness macular hole. These lesions can cause symptoms and affect visual function, and may be permanent structural changes.